Saint At Tashguzar Or Jingakli Ota Cemetery (Open Herald: Periodical of Methodical Research, 2024)
This article talks about the shrine of Jingakli father, located in the Guzor district of Kashkadarya region, and its place in the pilgrimage tourism of the Guzor district. Also, it is said that it is different from similar shrines located in the district and that it needs new scientific research